1994
DOI: 10.1007/bf02012178
|View full text |Cite
|
Sign up to set email alerts
|

Enterocolitis following endorectal pull-through procedure in children with Hirschsprung's disease

Abstract: The enterocolitis following a pull-through in Hirschsprung's disease can be life-threatening and difficult to distinguish clinically from gastroenteritis and post-operative complications. We reviewed retrospectively the abdominal radiographs in our series to identify specific radiographic characteristics of this syndrome in this population. A total of 55 episodes of enterocolitis with an abdominal series at presentation were located in the files of 43 patients following pull-through surgery for Hirschsprung's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
3

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 7 publications
0
8
0
3
Order By: Relevance
“…Our own experience with HAEC confirms the above findings. [1][2][3][4] Recent data from our institution have suggested that MUC-2, the predominant mucin gene, is markedly reduced in patients with Hirschsprung's disease and is absent in patients with HAEC. MUC-2 has been shown to be important in preventing bacterial translocation.…”
mentioning
confidence: 97%
“…Our own experience with HAEC confirms the above findings. [1][2][3][4] Recent data from our institution have suggested that MUC-2, the predominant mucin gene, is markedly reduced in patients with Hirschsprung's disease and is absent in patients with HAEC. MUC-2 has been shown to be important in preventing bacterial translocation.…”
mentioning
confidence: 97%
“…Radiographs typically will show air fluid levels and the absence of air in the distal rectosigmoid colon [68]. Pneumatosis intestinalis also may be seen on radiograph [64,68]. Spontaneous perforation is estimated to occur in about 3% of patients [66].…”
Section: Clinical Presentationmentioning
confidence: 98%
“…It is associated with fever, abdominal distention, bilious vomiting, explosive diarrhea, volume depletion, and shock [63,64]. Radiographs typically will show air fluid levels and the absence of air in the distal rectosigmoid colon [68]. Pneumatosis intestinalis also may be seen on radiograph [64,68].…”
Section: Clinical Presentationmentioning
confidence: 99%
“…[175][176][177][178] Most surgeons with substantial experience in the treatment of Hirschsprung's disease have been through the frustrating experience of some patients experienc-ing enterocolitis, whereas other patients who undergo the operation with the same technique behave like normal children. Postoperative Enterocolitis.-Even with a technically correct operation, enterocolitis may occur after the operation.…”
Section: Short-and Long-term Problemsmentioning
confidence: 99%